2013
DOI: 10.1124/jpet.113.209452
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic P2X7 Receptors Mediate Cell Death in Mouse Cerebellar Astrocytes in Culture

Abstract: The brain distribution and functional role of glial P2X7 receptors are broader and more complex than initially anticipated. We characterized P2X7 receptors from cerebellar astrocytes at the molecular, immunocytochemical, biophysical, and cell physiologic levels. Mouse cerebellar astrocytes in culture express mRNA coding for P2X7 receptors, which is translated into P2X7 receptor protein as proven by Western blot analysis and immunocytochemistry. Fura-2 imaging showed cytosolic calcium responses to ATP and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…As such, inhibition of the P2X7R offers protection against ATP-mediated cell death in a number of cells expressing the P2X7R [12], [30], [36]. Therefore, C23, C40 and C60 compounds were finally tested for their effectiveness in preventing ATP-induced cell death in hP2X7R-expressing HEK293 cells to provide further supporting evidence for their action on the hP2X7R.…”
Section: Resultsmentioning
confidence: 99%
“…As such, inhibition of the P2X7R offers protection against ATP-mediated cell death in a number of cells expressing the P2X7R [12], [30], [36]. Therefore, C23, C40 and C60 compounds were finally tested for their effectiveness in preventing ATP-induced cell death in hP2X7R-expressing HEK293 cells to provide further supporting evidence for their action on the hP2X7R.…”
Section: Resultsmentioning
confidence: 99%
“…shows that 1 mM ATP, which activates ionotropic purinergic receptors of astrocytes(Salas et al, 2013), causes a larger increase in[Ca 2+ ] I than that produced by 100 μM ATP. The [Ca 2+ ] I signal decreases in absence of external Ca 2+ (Figure 2b).…”
mentioning
confidence: 93%
“…S16C), which has been shown to inhibit rat P2X7-mediated cation flux but not dye uptake (22), and to inhibit mouse P2X7-mediated cation flux but not cell death (23). We also found that calmidazolium blocked Caspase-1 activation by the cation-specific inflammasome agonist nigericin in these cells (fig.…”
mentioning
confidence: 99%